KELEKATAN DENGAN HEWAN PELIHARAAN SEBAGAI PREDIKTOR STATUS SEHAT MENTAL DAN KUALITAS HIDUP PADA DEWASA AWAL DI KOTA BANDUNG - Mega Santika, - (2020)
This study aims to determine predictors of pet attachment on mental health and quality of life. This research uses a quantitative approach with a correlational method. The sample in this study amounted to 307 early adulthood aged 18-25 years who raise dogs and cats or both in Bandung. The subject of this research uses non-probability techniques, namely using purposive sampling technique, with the characteristics of the subject that have been determined by the researcher. This research uses 3 measuring instruments. To measure the pet attachment using the Lexington Attachment to Pet Scale (LAPS) measuring instrument, it consists of 20 items with a reliability coefficient of 0.91. To measure mental health using the Positive Mental Health Questionnaire (PMHQ) measurement tool, this measuring instrument consists of 39 items with the reliability coefficient of this measuring instrument is 0.92. Measure the quality of life using a quality of life measuring instrument using the Indonesian Quality of Life (KHI) measuring instrument is the development of a quality of life measuring instrument that adapts to the conditions in Indonesia which consists of 30 items. KHI has Alpha reliability of 0.88. The analysis technique used in this study to answer the hypothesis is regression analysis. The type of regression analysis used in this research is simple linear regression. Simple linear regression was used to test predictors of pet attachment on mental health and pet attachment on quality of life. The results of this study are pet attachment cannot be a predictor of mental health and pet attachment can be a predictor of quality of life in early adulthood in Bandung. Keywords: Early Adulthood, Mental Health, Pet Attachment, Quality of Life.